2004
DOI: 10.1007/s00534-003-0881-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined devascularization and proximal splenorenal shunt: is this a better option than either procedure alone?

Abstract: Combined devascularization and splenorenal shunt (PCDV + PSRS) significantly decreases portal venous flow and portal pressure, as well as maintaining hepatopedal flow, thus entailing fewer complications compared to either PCDV or PSRS. We aimed to determine the rationality of pericardial devascularization (PCDV) plus proximal splenorenal shunt (PSRS) for cirrhotic patients with portal hypertension with variceal bleeding, using a duplex sonography study of the effects of the different surgical procedures (PCDV,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Shunting and devascularization are the two main strategies based on different hemodynamic theories, and they have been suggested to be combined to reduce the PHT in liver cirrhotic patients [18]. Effects of devascularization alone and combined procedure on portal hemodynamics have been compared 11,17 ; however, data on the incidence of postoperative PVT are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Shunting and devascularization are the two main strategies based on different hemodynamic theories, and they have been suggested to be combined to reduce the PHT in liver cirrhotic patients [18]. Effects of devascularization alone and combined procedure on portal hemodynamics have been compared 11,17 ; however, data on the incidence of postoperative PVT are limited.…”
Section: Discussionmentioning
confidence: 99%
“…PSS+PAD, ahead of schedule replaces spontaneous shunt, which slowly occurs after PAD with artificial shunt in operation. Combined devascularization and splenorenal shunt (PAD+PSS) significantly decreases portal venous flow and portal pressure, as well as maintaining hepatopetal flow, thus entailing fewer complications compared to either PAD or PSS, some scholars even advocated that PSS+PAD could be a primary selection in the operations for portal hypertension [53,54] . Compared to PSS or PAD, PSS+PAD prolongs operation time, aggravates surgical trauma, and damages liver function, which are the reasons why PSS+PAD cannot be generally performed.…”
Section: Combined Pss+padmentioning
confidence: 99%
“…Failure risk factors include Child C cirrhosis, high final portal pressure despite recanalization, splenic vein or SMV involvement and untreated hepatic malignancy [28,29]. Kim et al found a patency period of 30.1 卤 25.6 months in their 11 patients with postoperative benign portal vein stenosis [23].…”
Section: Discussionmentioning
confidence: 99%
“…The results of many studies on percutaneous transhepatic portal vein stent placement suggest that the procedure is safe and has few major complications [1,3,6,8,23,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation